2008
DOI: 10.1186/1752-4458-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Job stress among community health workers: a multi-method study from Pakistan

Abstract: Background: In low income countries, the task of providing primary health care is often the responsibility of community health workers. In Pakistan, community workers called Lady Health Workers (LHW) deliver basic health care at the doorstep in the rural areas and urban slums. Evaluations show that it is a successful programme but point out inconsistencies in the quality of service provided. In order achieve this, it would be important to obtain the workers' viewpoint on their job-description, the problems the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 12 publications
5
80
1
5
Order By: Relevance
“…These factors aff ect LHW job stress and performance. 9,31 The investigators had little control over local managers, several of whom were transferred into and out of the district several times. Even the robust federal LHW programme saw three changes of leadership at the federal and four at the provincial level between 2004 and 2008.…”
Section: Discussionmentioning
confidence: 99%
“…These factors aff ect LHW job stress and performance. 9,31 The investigators had little control over local managers, several of whom were transferred into and out of the district several times. Even the robust federal LHW programme saw three changes of leadership at the federal and four at the provincial level between 2004 and 2008.…”
Section: Discussionmentioning
confidence: 99%
“…The author suggested that specific illnesses appear to be associated with burnout, including colitis, gastrointestinal problems and drug and alcohol addiction, among others. Developed countries face different challenges than do non-developed countries, specifically, economic [42] and cultural differences, which have been considered in stress research [43] . Nonetheless, it is difficult to describe the occupational psychological-stress classifications, levels, exposure durations, exposure limits, sensitivity, etc.…”
Section: Job Occupation and Psychologi-cal Stressmentioning
confidence: 99%
“…Hence, research into job-related stress has increased in recent years (Whetten and Cameron, 1991). Notably, previous studies have shown that work stress can be physically and mentally harmful to workers and it is related to physical condition, organizational structure, interpersonal conflict, personal characteristics and nature of work , Haq et al, 2008Lath, 2010). There is also evidence in the literature suggesting that occupational stress has manifested itself in unsafe working practices, decrease in the quantity and quality of performance at work and reduction in performance accuracy (Loosemore and Waters, 2004;Melia and Becerril, 2007;Halkos and Bousinakis, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Work stress is known to impact negatively on productivity and job satisfaction among workers in different professions (McVicara, 2003;Ng et al, 2005;Haq et al, 2008;Lath, 2010). It is also believed to be a major contributor to absenteeism, low employee morale, high accident and turnover rates as well as increasing medical expenses of many organizations (Wahab, 2010).…”
Section: Introductionmentioning
confidence: 99%